Biodiversity and Modernization in Four Coffee-producing Villages of Mexico - Catherine Potvin; Claire T. Owen; Said Melzi; Pierre Beaucage (Ecology and Society, 2005)
Coffee cultivation in Mexico is important both to people's livelihood and to the conservation of plant species richness. Management ranges from traditional shaded coffee garden to "modern" unshaded monoculture. Recognizing the importance of both livelihoods and biodiversity, we examined how the plant diversity of coffee gardens was affected by a certain form of "modernization," which, from 1974 to 1988, was strongly promoted through the intervention of the Mexican State and international development agencies: that is, planting high-yield varieties (HYV) with little or no shade and using chemical fertilizers and herbicides. Our research also sought to use ecological statistical approaches to understand modifications in a traditional human ecosystem. It centered on two questions: (1) How do differences in coffee production, along a gradient of modernization, affect plant species richness? (2) What is the relative importance of ecological vs. socioeconomic factors in explaining plant diversity in individual coffee gardens? To answer these questions, we compared floristic diversity of four coffee-growing villages differing in ecological context and in the degree to which they were modernized. The two poles of our traditional/modern gradient are the villages of Tierra Colorada, where the traditional Mexican variety of coffee bushes, called café criollo ("creole coffee") is not grown anymore, and San Lorenzo, where all the farms that we studied only grew criollo coffee. Discriminant analysis suggests that modernization can be viewed as a syndrome of traits, among which farmer's education and household size are important components. Overall, the small coffee gardens studied harbor high plant species richness. Our results show a significant negative effect of modernization on plant species richness in San Miguel, one of the four villages studied. Although ecological characteristics were prevalent in explaining species richness, the redundancy analyses (RDA) emphasized the complementary importance of socioeconomic factors in explaining variation in plant species richness in coffee gardens within a given community. Apparently, this importance increases as modernization sets in. In order words, when coffee gardens are managed in a traditional way, as in San Lorenzo, ecological factors are sufficient to explain most variation in species richness. However, in villages where cultivation includes modern practices, these practices exert a direct impact on species richness. The key loading factors for the socioeconomic RDAs were coffee variety, fertilizer, and age of coffee bushes. Our successful methodological approach suggests that numerical ecology offers promising tools for the analysis of human impacted ecosystems.